Crystal structures of [XnE]+[(η7-C7H7)Mo(CO)2GaI3]- (XnE = (thf)4Li, Cy3PH) - Coombs, N; Aldridge, S; Thompson, A; Male, L; Hursthouse, M (2007)
The crystal structures of [XnE]+[(η7-C7H7)Mo(CO)2GaI3]- [XnE = (C4H8O)4Li (1), (C6H11)3PH (2)] are reported, revealing: (1) monoclinic, P21/c, a = 11.2388(1), b = 17.3201(3), c = 17.5473(2)Å, β = 101.623(1)°, Z = 4, R = 0.038 and wR2 = 0.090 for 7614 observed reflections [I>2σ(I)]; (2) monoclinic, P21/n, a = 9.2979(5), b = 18.4632(8), c = 19.9789(9)Å, β = 99.325(3)°, Z = 4, R = 0.073 and wR2 = 0.184 for 5554 observed reflections [I > 2σ (I)]. 2007 © The Japan Society for Analytical Chemistry.